Trump: Just a Berlusclone - Gerardo Papalia (PORTAL: Journal of Multidisciplinary International Studies, 2017)
Berlusconi and Trump share many analogies, but perhaps the most cogent of them is their ability to master new media. They are both ubiquitous on television while Trump also rides the social media wave. Their success reflects and reinforces a new mediatic paradigm: the Digisphere. They are not notable as individuals in themselves but as simulacra of what may become a long procession of future political leaders.